ATR-mediated phosphorylation of DNA polymerase η is needed for efficient recovery from UV damage. - Göhler, T; Sabbioneda, S; Green, C; Lehmann, A (2011)
DNA polymerase η (polη) belongs to the Y-family of DNA polymerases and facilitates translesion synthesis past UV damage. We show that, after UV irradiation, polη becomes phosphorylated at Ser601 by the ataxia-telangiectasia mutated and Rad3-related (ATR) kinase. DNA damage-induced phosphorylation of polη depends on its physical interaction with Rad18 but is independent of PCNA monoubiquitination. It requires the ubiquitin-binding domain of polη but not its PCNA-interacting motif. ATR-dependent phosphorylation of polη is necessary to restore normal survival and postreplication repair after ultraviolet irradiation in xeroderma pigmentosum variant fibroblasts, and is involved in the checkpoint response to UV damage. Taken together, our results provide evidence for a link between DNA damage-induced checkpoint activation and translesion synthesis in mammalian cells.